2020
DOI: 10.2147/cmar.s271021
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA DARS-AS1 Contributes to Prostate Cancer Progression Through Regulating the MicroRNA-628-5p/MTDH Axis</p>

Abstract: Purpose DARS antisense RNA 1 (DARS-AS1) is a long non-coding RNA that has been validated as a critical regulator in several human cancer types. Our study aimed to determine the expression profile of DARS-AS1 in prostate cancer (PCa) tissues and cell lines. Functional experiments were conducted to explore the detailed roles of DARS-AS1 in regulating PCa carcinogenesis. Furthermore, the detailed mechanisms by which DARS-AS1 regulates the oncogenicity of PCa cells were uncovered. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Several variants, mutations, or even genomic rearrangements (TMPRSS2-ERG fusion is the most common in human prostate cancer, but is absent in small cell carcinoma of the bladder) are involved in pathophysiological situations correlated with AR signaling pathways; the complex interaction of each protein in a specific context may lead to different results, and represents a new pharmacological target for these pathologies, including bladder cancer [29]. New strategies that modulate AR signaling are developing, as demonstrated in the studies with long noncoding RNAs (lncRNAs), microRNAs, enhancer RNAs (eRNAs), and others [30][31][32][33]. The AR interacts with enzymes (cofactors) involved in the regulation of histone methylation, such as lysine-specific demethylase 1 (LSD1), KDM4B, KDM5B, KDM7A, EZH2, SMYD3 and PRMT5.…”
Section: Activation Of Androgen Receptor and Cofactorsmentioning
confidence: 99%
“…Several variants, mutations, or even genomic rearrangements (TMPRSS2-ERG fusion is the most common in human prostate cancer, but is absent in small cell carcinoma of the bladder) are involved in pathophysiological situations correlated with AR signaling pathways; the complex interaction of each protein in a specific context may lead to different results, and represents a new pharmacological target for these pathologies, including bladder cancer [29]. New strategies that modulate AR signaling are developing, as demonstrated in the studies with long noncoding RNAs (lncRNAs), microRNAs, enhancer RNAs (eRNAs), and others [30][31][32][33]. The AR interacts with enzymes (cofactors) involved in the regulation of histone methylation, such as lysine-specific demethylase 1 (LSD1), KDM4B, KDM5B, KDM7A, EZH2, SMYD3 and PRMT5.…”
Section: Activation Of Androgen Receptor and Cofactorsmentioning
confidence: 99%
“…Additionally, mounting evidence indicates the involvement of the ceRNA network in PCa regulation. Fan et al suggested that lncRNA DARS1 Antisense RNA 1 (DARS-AS1) promotes PCa development via the DARS-AS1/miR-628-5p/MTDH ceRNA network [20]. Zhang et al identi ed that lncRNA OIP5-AS1 operates via a ceRNA mechanism in PCa by adsorbing miR-128-3p, leading to increased expression of SLC7A11 and hence promoting PCa progression and ferroptosis resistance [21].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the protein-coding genes above, DARS-AS1 is a long noncoding RNA (lncRNA). The majority of studies investigating this lncRNA have been related to its role in cancer, where it acts to regulate the expression of several microRNAs, including miR-129, miR-194-5p, miR-532-3p, and miR-628-5p [ 38 – 41 ], as well as the protein RNA-binding motif protein 39 (RBM39) [ 42 ]. As a number of studies have highlighted the importance of microRNAs in antidepressant response [ 43 , 44 ], it seems plausible that the role of DARS-AS1 in escitalopram response involves modulation of microRNA expression.…”
Section: Discussionmentioning
confidence: 99%